1985
DOI: 10.1177/004728758502400104
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Novelty in the Pleasure Travel Experience

Abstract: Despite an extensive literature on novelty-seeking and the intuitive appeal of vacation behavior as a setting for its observation, the significance of a pleasure trip that is familiar or "commonplace" as opposed to one that is "novel" has not been investigated. The purpose of this study is to describe novel versus commonplace trips and to explore behavioral and demographic differences between travelers who experience different levels of novelty.Pleasure trips are taken in anticipation of a set of benefits that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
2
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(155 citation statements)
references
References 14 publications
6
141
2
6
Order By: Relevance
“…Lepp and Gibson (2003) were the first to systematically investigate the influence of tourist role and their preference for novelty or familiarity on risk perception. The need for novelty was found to be related to the individual lifestyle (Bello & Etzel, 1985) as well as personality (Plog, 1974). One of the most cited works associated with tourists' risk perception would be the classical work of Plog (Korstanje, 2009;Kozak et al, 2007;Lepp & Gibson, 2003;Pizam et al, 2004;Reisinger & Mavondo, 2005;Sönmez & Graefe, 1998b).…”
Section: The Antecedents Of Risk Perceptionmentioning
confidence: 99%
“…Lepp and Gibson (2003) were the first to systematically investigate the influence of tourist role and their preference for novelty or familiarity on risk perception. The need for novelty was found to be related to the individual lifestyle (Bello & Etzel, 1985) as well as personality (Plog, 1974). One of the most cited works associated with tourists' risk perception would be the classical work of Plog (Korstanje, 2009;Kozak et al, 2007;Lepp & Gibson, 2003;Pizam et al, 2004;Reisinger & Mavondo, 2005;Sönmez & Graefe, 1998b).…”
Section: The Antecedents Of Risk Perceptionmentioning
confidence: 99%
“…Hirschman (1984) asserts that there are basically three stages of experience seeking: (i) cognitive; (ii) sensation; and (iii) novelty. Otto and Ritchie (1996) built on earlier studies by Havlena and Holbrook (1986), Holbrook and Hirschman (1982), and Bello and Etzel (1985), among others, by using an empirical study of 339 tourists to identify six fundamental dimensions of the experience construct: a Hedonic Dimension, an Interactive or Social Dimension, a Novelty Seeking or Escape Dimension, a Comfort Dimension, a Safety Dimension, and a Stimulating or Challenge Seeking Dimension. It argues those seeking to provide tourists with a quality experience should consider the merits of providing visitors with each and/or all of these six components of 'the tourism experience'.…”
Section: Typology Of Experiencesmentioning
confidence: 99%
“…Hightower et al [21] pointed out that affective factors, such as hedonics and novelty, are integral conceptualizations of perceived value. Many other studies have shown that longing for more novel experiences generates more pleasure and perceived value [22,23]. In addition to the effect on pre-purchase choice, perceived value also affects tourists' willingness to recommend a vacation as well as their intention to revisit [24,25].…”
Section: Methodology Theoretical Background and Hypothesesmentioning
confidence: 99%